Virus-like particles: a self-assembled toolbox for cancer therapy. (June 2022) - Shahrivarkevishahi, A.; Hagge, L.M.; Brohlin, O.R.; Kumari, S.; Ehrman, R.; Benjamin, C.; Gassensmith, J.J.
Abstract: Nanoparticle-based therapeutics have been applied in a broad range of clinical and preclinical applications from diagnosis to treatment for cancer. A wide range of synthetic and naturally occurring materials, such as polymers, metal oxides, silicate, liposomes, and carbon nanotubes, have been developed to overcome key barriers in small molecule therapeutics, including intracellular trafficking, cell/tissue targeting, poor biodistribution, and low efficiency. Virus-like particles—engineered and non-infectious self-assembling systems based on viral nanostructures—are new approach toward overcoming these limitations, as they are a protein-based nanomaterial that closely mimics the highly symmetrical and polyvalent conformation of viruses while lacking the viral genomes. Their innate biocompatibility, biodegradability, monodispersity, mild immunogenicity, and safety combined with the capacity to chemically modify the interior and exterior surfaces of these systems offer scientists a highly customizable tool to design and engineer multicomponent therapeutic agents. In this review, we discuss how these systems have been used in a wide array of cancer treatments, including phototherapy, immunotherapy, gene therapy, and chemotherapy. Highlights: We review cutting edge science at the interface of chemistry and biotechnology and bioengineering. We show examples of how viral nanoparticles can be used as a versatile platform for a variety of cancer treatments. We review many types of VLPs and their unique potential in different therapeutic fields.